Test of lepton universality with Λ0b → pK- ℓ+ ℓ- decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; D'Argent, Philippe; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2020)
The ratio of branching fractions of the decays Λ0b → pK−e+e− and Λ0b → pK−μ+μ−, R-1pK, is measured for the first time using proton-proton collision data corresponding to an integrated luminosity of 4.7 fb−1 recorded with the LHCb experiment at center-of-mass energies of 7, 8 and 13 TeV. In the dilepton mass-squared range 0.1 < q2 < 6.0 GeV2/c4 and the pK− mass range m(pK−) < 2600 MeV/c2, the ratio of branching fractions is measured to be R-1pK=1.17+0.18-0.16+- 0.07, where the first uncertainty is statistical and the second systematic. This is the first test of lepton universality with b baryons and the first observation of the decay Λ0b → pK−e+e−.